Pelatihan Kemampuan Menyimak dan Membaca Melalui Storytelling dan Pengadaaan Pojok Baca di Desa Kutaraja - Agustiana, Vina; Nugroho, M. Aprianto Budie; Azka, Fina Saeila; Sulaksana, Johan (Yayasan Kajian Riset Dan Pengembangan Radisi, 2025)
This community service activity aims to enhance listening and reading skills among elementary school students through storytelling methods and the establishment of reading corners in Kutaraja Village, Maleber District, Kuningan Regency. The primary issue addressed is the low reading interest and literacy skills among children. The methods employed include initial observation, community socialization, training for volunteers and educators, as well as the implementation of technology for access to reading materials. The execution of the program involves a dedicated team of lecturers and students, alongside active participation from local government, parents, and students. Results indicate an increase in reading interest and community engagement, with the reading corner serving as an effective learning resource. Through this initiative, the community is expected to foster a sustainable literacy culture. The conclusion emphasizes the importance of collaboration among various stakeholders in supporting education and literacy, as well as the necessity for sustainable management of the reading corner to ensure long-term success.